Is There Room for the Use of Animals in the Teaching of Biology? Reflections from an Ecological and Multilevel Perspective - De Giuseppe, Bianca Camila (2020)
In this essay, we will approach the problems related to the manipulation of animals for the teaching of biology. Based on an ecological model, a hypothesis is held that the use of animals for the teaching of biology is not only unethical, but also not profitable, effective, and it does not favor the development of fundamental social skills, such as empathy, even reaching such an extent that students exposed to these situations can manifest adverse psychological effects. To support this statement, we will go to theoretical, practical, and experimental evidence. We conclude, from our analysis, that the elimination of practices that involve the manipulation of animals would favor not only the animals themselves and the students, but society as a whole, since they would be teaching from the first years of schooling, students with ecological intelligence and animal empathy, traits that favor a friendly and ethical treatment towards the environment.